Kesejahteraan Psikologis Remaja Korban Body Shaming - Nurul Aisyah Sartika; Yusi Riksa Yustiana; Ipah Saripah (Psychocentrum Review, 2021)
The purpose of the study was to describe the psychological well-being profile of adolescent victims of body shaming. The research method is descriptive analysis with a quantitative approach. The instrument uses Ryff's Psychological Well-Being Scale and body shaming questionnaire. The distribution of the questionnaire was carried out with the help of the Google Form application with a total of 30 respondents. 40% of respondents victims of body shaming indicate good enough psychological well-being, 26.67% of respondents indicate a good category, 26.67% of respondents indicate a very good category, and 6.67% of respondents indicate a poor category.  Adolescent victims of body shaming based on the percentage of the total score on each dimension of psychological well-being the largest is purpose in life (18.62%), followed by the autonomy dimension (17.80%), personal growth (17.72%), positive relations with others (16.08%), environmental mastery (16.08%), and the smallest percentage was obtained by self-acceptance dimension (13.70%). There is no significant difference in psychological well-being of adolescent victims of body shaming based on gender and age.